2015
DOI: 10.11646/zootaxa.4006.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular variation in Tylototriton (Caudata: Salamandridae) in Laos, with description of a new species

Abstract: The salamandrid genus Tylototriton is poorly known in Laos, with one described species and unverified reports of two others. We undertook new fieldwork and obtained samples of Tylototriton at six localities across northern Laos during 2009-2013. Bayesian phylogenetic analysis of mitochondrial DNA, principal component analyses of 13 mensural characters, and qualitative morphological comparisons with samples from across the geographic range of Tylototriton were performed. Samples from Laos fell into four molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 16 publications
1
26
1
Order By: Relevance
“…Twelve Tylototriton s.l. species have been described in the past five years ( Zhao et al, 2012 ; Shen, Jiang & Mo, 2012 ; Hou, Li & Lu, 2012 ; Nishikawa et al, 2013 ; Nishikawa, Matsui & Nguyen, 2013 ; Nishikawa, Matsui & Rao, 2014 ; Yang et al, 2014 ; Khatiwada et al, 2015 ; Phimmachak, Aowphol & Stuart, 2015 ). But within all nominal species, T. daweishanensis was argued to be synonym of T. yangi ( Nishikawa et al, 2015 ), and T. shanjing was argued to be synonym of T. verrucosus ( Zhang et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Twelve Tylototriton s.l. species have been described in the past five years ( Zhao et al, 2012 ; Shen, Jiang & Mo, 2012 ; Hou, Li & Lu, 2012 ; Nishikawa et al, 2013 ; Nishikawa, Matsui & Nguyen, 2013 ; Nishikawa, Matsui & Rao, 2014 ; Yang et al, 2014 ; Khatiwada et al, 2015 ; Phimmachak, Aowphol & Stuart, 2015 ). But within all nominal species, T. daweishanensis was argued to be synonym of T. yangi ( Nishikawa et al, 2015 ), and T. shanjing was argued to be synonym of T. verrucosus ( Zhang et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The massive destruction of the natural habitat for the whole genus Tylototriton is a major threat in Asia which is explaining the important decrease of each species this last decade (Stuart et al, 2004(Stuart et al, , 2008Phimmachak et al, 2015;Hernandez, 2015Hernandez, , 2016aIUCN, 2017;AmphibiaWeb, 2018). Most of the species known and described recently are not distributed within protected areas and are not listed on the World or national IUCN Red Lists (Fei et al, 2006(Fei et al, , 2012Stuart et al, 2008;Raffaëlli, 2013;Hernandez, 2015;Khatiwada et al, 2015;Fei & Ye, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…They are one of the few lineages of sala-They are one of the few lineages of salamanders that appear in the tropical regions, with a poorly known ecology and natural history . Tylototriton and Echinotriton comprise more than 27 species with many undescribed taxa, and most of them are endangered pri-marily because of the habitat destruction in South-Eastern Asia (Seglie et al, 2003;Phimmachak et al, 2015;Hernandez, 2015Hernandez, , 2016bQian et al, 2017). During the last decade, new populations were identified and described in the Province of Yunnan, China, where an important evolutionary radiation occurred resulting from the Pleistocene glaciation among the «Tylototriton verrucosus» group, known as the subgenus Tylototriton (Hou et al, 2012;Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of newt diversity in the region has changed dramatically in recent years, with the number of species recognised from the region increasing threefold since 2000 (Frost, 2016). This is a result of increased survey effort and the incorporation of molecular data in resolving species boundaries in the morphologically conserved taxa (Le et al, 2015;Nishikawa et al 2013Nishikawa et al , 2014Phimmachak et al, 2015a;Stuart et al 2010). Undescribed diversity likely remains (Nishikawa et al, 2013, Sparreboom, 2014 and the basic biology, ecology and true conservation status of known Southeast Asian newts remains poorly-known (Phimmachak et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Of the nine assessed species, five are considered threatened with extinction, and three are near threatened (Table 1). Tylototriton verrucosus is the only species of newt in Southeast Asia that is currently considered Least Concern, but since the assessment was performed (van Dijk et al, 2009), new research has shown that this species actually consists of a a complex of several species, each having narrower ranges and thus more likely to be threatened (e.g., Nishikawa et al, 2013Nishikawa et al, , 2014Phimmachak et al, 2015a;Le et al, 2015;). For example, one recently described species previously thought to be T. verrucosus, T. shanorum, is endemic to Myanmar (Nishikawa et al, 2014), where it is currently known only from a few ponds at risk of development (G. Wogan, pers.…”
Section: Introductionmentioning
confidence: 99%